Principios nacionales e internacionales en el marco de la protección de datos personales: deficiencias, recomendaciones - Piccirilli, María Eugenia (2015)
Personal data is usually given in everyday situations. This paper will analyze if Argentina has an efficient legislation that protects the right to privacy, honor and intimacy. Moreover it will review the most important international foundations for gathering information without infringing these rights. Finally it will suggest some guidelines to improve the existing legislation.